2015
DOI: 10.1109/tit.2015.2429611
|View full text |Cite
|
Sign up to set email alerts
|

$NP/CMP$ Equivalence: A Phenomenon Hidden Among Sparsity Models $l_{0}$ Minimization and $l_{p}$ Minimization for Information Processing

Abstract: Abstract-In this paper, we have proved that in every underdetermined linear system Ax = b there corresponds a constant p * (A, b) > 0 such that every solution to the lp-norm minimization problem also solves the l0-norm minimization problem whenever 0 < p < p * (A, b). This phenomenon is named N P/CM P equivalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Theorem 2 is the main theorem in [7]. Obviously, this theorem qualitatively proves the effectiveness of solving the original -minimization problem via -minimization.…”
Section: Preliminariesmentioning
confidence: 69%
See 4 more Smart Citations
“…Theorem 2 is the main theorem in [7]. Obviously, this theorem qualitatively proves the effectiveness of solving the original -minimization problem via -minimization.…”
Section: Preliminariesmentioning
confidence: 69%
“…It is shown that is a continuous function in when , where is the smallest number of columns from A that are linearly dependent. Therefore, if for some fixed A and k , then there exists a constant such that for , that is, every k -sparse vector can be recovered via both -minimization and -minimization for , which is a corollary of the main theorem in [7]. …”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations